Tourism Crisis Management in Jordan: an Overview - Abu Tayeh, Sultan Nayef; Mustafa, Mairna Hussein (Advances in Social Sciences Research Journal, 2018)
The Arab Spring had its negative effects on tourism in the region of the Middle East. This research note aims to make an overview of strategies adopted by Jordanian tourism public authorities to repair the destination image in time of crisis; a short discussion is then made on political crisis management, followed then by giving recommendations to enhance the performance of these authorities in dealing with such crisis.